Green approach for the decoration of Pd nanoparticles on graphene nanosheets: an in situ process for the reduction of C-C double bonds and a reusable catalyst for the suzuki cross-coupling reaction - Hussain, Najrul; Borah, Ashwini; Darabdhara, Gitashree; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (New Journal of Chemistry, 2015)
A new strategy for in situ synthesis of palladium nanoparticles (Pd NPs) decorated on reduced graphene oxide (rGO) nanosheets with controlled size and shape is reported. This strategy was designed as three processes in one pot, namely, (a) reduction of graphene oxide, (b) formation of Pd NPs on the rGO nanosheets and (c) simultaneous reduction of olefin. In this synthesis process, a hydrogen atmosphere was used to develop the Pd NPs-rGO nanocatalyst, which is reusable and easily separable. The influence of the size and morphology of the Pd-rGO-H-2 catalyst on the catalytic activity in the Suzuki cross-coupling reaction was investigated by comparing with other catalysts, Pd-rGO-As and Pd-rGO-Gl, and they were synthesized by different reducing agents, ascorbic acid and glucose, respectively. The catalysts were characterized by electron microscopy (HRTEM, SEM), FT-IR, XRD and XPS. The Pd-rGO-H-2 catalyst was found to possess excellent catalytic activity and recyclability in the Suzuki cross-coupling reaction under mild reaction conditions.

Sunlight assisted degradation of dye molecules and reduction of toxic Cr(VI) in aqueous medium using magnetically recoverable Fe3O4/reduced graphene oxide nanocomposite - Boruah, Purna K.; Borthakur, Priyakshree; Darabdhara, Gitashree; Kamaja, Chaitanya Krishna; Karbhal, Indrapal; Shelke, Manjusha V.; Phukan, Pallabi; Saikia, Dulen; Das, Manash R. (RSC Advances, 2016)
In view of the significant impact of magnetically recoverable catalysts in photocatalytic applications, Fe3O4/reduced graphene oxide (rGO) nanocomposite photocatalyst was synthesized by adopting an eco-friendly solution chemistry approach and has been characterized by high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and photoluminescence (PL) spectroscopy. Fe3O4/rGO nanocomposite is efficiently utilized towards photocatalytic degradation of carcinogenic and mutagenic cationic as well as anionic dye molecules namely methyl green (MG), methyl blue (MB) and rhodamine B (RhB) under direct sunlight irradiation. The Fe3O4/rGO nanocomposite also demonstrated excellent photocatalytic reduction of aqueous Cr(VI) solution to nontoxic aqueous Cr(III) solution of more than 96% within 25 min under sunlight irradiation. Moreover, reusability of the magnetically recovered photocatalyst was studied efficiently up to 10 cycles in the degradation process. The catalyst was also characterized after the degradation of the dye molecule and the particle size of the Fe3O4 nanoparticles on the rGO sheets remained unchanged. The present investigation focuses on the importance of the use of Fe3O4/rGO nanocomposite towards photocatalytic degradation of waste water containing organic dye pollutants and toxic Cr(VI), as an easily recoverable and reusable photocatalyst with potential for many environmental remediation applications.